Digital Marketing's Effect On Purchase Decisions Through Customer Satisfaction - Ilham Ilham; Warkianto Widjaja; I Nyoman Tri Sutaguna; Arief Yanto Rukmana; Muhammad Yusuf (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
In order to investigate the impact of digital marketing, service quality, and product on purchasing decisions at PT. Alunicorn, 249 people were questioned. Customer satisfaction was used as an intermediary variable. retrieval method based on the sample's evaluation of the target population. The analytical technique used in this work was SEM AMOS 23. The hypothesis states that whereas service quality has no impact on purchasing decisions through satisfaction, digital marketing and product quality have a positive impact on consumer satisfaction and purchasing decisions.